Raman spectroscopy of thin DLC film deposited by plasma electrolysis process - Habibi, A.; Mousavi Khoie, S.M.; Mahboubi, F.; Urgen, M. (Elsevier BV, 2017)
Abstract A thin diamond-like carbon film was deposited on Ni substrate by plasma electrolytic deposition in ethanol-water solution. The thickness of the deposited carbon film was measured about 40–60 nm by using glow discharge optical emission spectroscopy and optical profilometer. The characterization of film structure by Raman spectroscopy showed the superposition of Raman features on a photoluminescence background because of low thickness of the deposited film. The surface enhanced Raman scattering technique by coating the carbon film with Au nanoparticles and high power laser in Raman spectroscopy was used as Raman intensity enhancer. Amplified Raman signals by using both techniques showed formation of diamond-like carbon film and various sp2 and sp3-bonded compositions on grain boundaries of nanostructure carbon coating. The Raman spectrum of the Au coated carbon film revealed an additional band at 2150 cm− 1, which is related to the carbyne structure whereas carbyne band could not be detected using high power laser. Comparison of Raman spectra at two wavelengths of 632.8 and 785 nm showed changes in the intensity and position of Raman bands. Likewise, the 785 nm laser wavelength excitation has sufficient energy to enhance the scattering from the grain boundary structures.